Determinant Analysis Of Consumer Buying In Semolowaru Surabaya PKL Center - Egan Evanzha Yudha Amriel; Kiki Nuriska Denhas; Reiga Ritomiea Ariescy (Universitas Muhammadiyah Jember, 2019)
The form of attention of Surabaya city government to manage PKL or street merchant (Pedagang Kaki Lima) is to provide a culinary tourism center so that the PKL can sell orderly and many people will be interested to come to the PKL center. If we look at the current phenomenon, many of PKL culinary centers are few visitors so that some of the tenants are finally closed, this is unfortunate if the government Surabaya already spent a lot of funds to build the PKL center. The purpose of this research is to explore the interest of buying consumers because of the least visitors to the Semolowaru PKL center in Surabaya so that researchers can determine the marketing strategy that can be done at Semolowaru PKL center so many visitors and give more revenue for PKL. This research is a qualitative study with the Phenomenology model. Phenomenology seeks to uncover, learn and understand a phenomenon along with the distinctive and unique context experienced by the individual to the individual's